The Enthusiasm for Political Participation Among the Young Participants of the “Political School” Program at the Hilal Hilmawan Institute in Indramayu Regency - Dhea Amanda; Farida Nurfalah (Journal Research of Social Science, Economics, and Management, 2026)
Youth political participation is crucial for democratic sustainability, yet remains low due to apathy, negative stigma, and limited political education, making non-formal political education a strategic alternative to increase awareness and engagement. This research aims to produce an analysis of the enthusiasm for political participation of the young generation who participate in the Hilal Hilmawan Institute (HHI) Political School Program in Indramayu Regency, identify the obstacles they face, and examine the various efforts made to overcome these obstacles. A qualitative approach with the type of case study was used in this study where data was collected through in-depth interviews with key informants and supporters, direct observation, and literature review from relevant scientific journals and books. Thematic analysis techniques are used in the data analysis process and the results of the research provide clues that the HHI Political School Program has contributed to increasing the enthusiasm of the political participation of the younger generation as seen from their involvement in informal political activities, increasing interest and attention to political issues, and growing confidence to participate in political activities. The main obstacles that are still faced include the existence of negative societal stigma towards politics as well as structural factors while efforts are made to improve political literacy, strengthen social networks through the alumni community, and continue involvement in discussion rooms and socio-political activities.